Exploiting the exploiter: some violations of society’s expectations in Beyond the Horizon and The Housemaid - Marfo, Charles Ofosu; Yeboah, Philomena Abeka; Bonku, Lucy (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
This paper does a critical reading of Beyond the Horizon and The Housemaid and observes that the author, Amma Darko, seeks primarily to challenge prevailing and traditional views of motherhood held by African societies; i.e. motherhood and its associated activities such as caring, training and disciplining. Amma Darko sharply condemns this view and calls for a critical analysis of the nature of motherhood, especially in contemporary times. Agreeing with Amma Darko and taking issues raised by her even a little further, with snippets from the books, the paper brings to the fore the fact that the prevailing and traditional views of motherhood have inherent conflict with reality. That is to say, these views are carelessly assumed as problemfree. Within this context, we also critically bring into discussion the running theme of exploiting the exploiter in the two books within the framework of gender studies and queer theory. We also generally question the fixed categories of paradigms generated by normative ideology and conclude with the realisation that almost all mothers (and, for that matter, exhibition of womanhood) in these novels failed because of the wrong choices they made, which were basically and largely fuelled by challenging economic conditions.